Revisão sistemática do gênero Trichomycterus Valenciennes do sudeste do Brasil (Siluriformes: Loricarioidea: Trichomycteridae) - Vianna, Maria Anaïs Barbosa Segadas (2004)
Forty-four species of Trichomycterus Valenciennes, 1832 are included in a taxonomic revision encompassing species endemic to the Southeastern Brazil. All species were collected between Doce river basin, Espírito Santo state, and Ribeira do Iguape river basin, São Paulo state, including the Paraíba do Sul, upper São Francisco, upper Paraná river basins, and a series of adjacent smaller isolated basins situated in the delimited area. They are grouped into seven assemblages : group Alfa, diagnosed by opercular odontodes arranged obliquely, including T. brasiliensis Lutken, 1874, T. mimonha Costa, 1992, T. mirissumba Costa, 1992, T. potschi Barbosa & Costa, 2003, T. vermiculatus (Eigenmann, 1918), and more ten new species; group Beta diagnosed by a broad metapterygoid, including T. itatiayae (Ribeiro, 1906), and more three new species; group Gama diagnosed by the number of rays of pectoral-fin, including T. reinhardti (Eigenmann, 1918), and one new species; group Delta diagnosed by a long pectoral-fin filament, including T. alternatus (Eigenmann, 1917), T. longibarbatus Costa, 1992, and four new species; group Omega diagnosed by the reduced lenght of the head, and the morphology of the interopercular patch of odontodes, including only T. candidus (Ribeiro, 1949); group Zeta diagnosed by the high number of interopercular odontodes, including T. immaculatus (Eigenmann & Eigenmann, 1889), and three new species; and, group Sigma diagnosed by the position of the second supraorbital pore, including T. albinotatus Costa, 1992, T. auroguttatus Costa, 1992, T. florensis Ribeiro, 1943, T. goeldii Boulenger, 1896, T. travassosi (Ribeiro, 1949), T. zonatus (Eigenmann, 1918), and six new species.